The Entrepreneurial Finance of Fintech Firms and the Effect of Investments in Fintech Startups on the Performance of Corporate Investors - Chemmanur, Thomas J.; Imerman, Michael B.; Rajaiya, Harshit; Yu, Qianqian (Journal of Financial and Quantitative Analysis, 2025)
Abstract We analyze how corporate direct investments in fintech startups affect startup performance and that of investing firms. Corporate investment in fintech startups is associated with a greater likelihood of successful exit, more and higher-quality innovation, and a greater inflow of high-quality inventors. A stacked difference-in-differences analysis shows that direct investments enhance the operating performance and equity-market valuation of corporate investors in the financial services sector, but not those in the nonfinancial sector. We establish two channels that drive fintech startups’ performance improvements: strategic alliance formation between investors and startups, and enhanced startup monitoring by corporate investors.